Femtosecond dynamics of a drug–protein complex: Daunomycin with Apo riboflavin-binding protein - Zhong, Dongping (The National Academy of Sciences, 2001)
In this contribution, we report studies of the primary dynamics of the drug–protein complexes of daunomycin with apo riboflavin-binding protein. With femtosecond resolution, we observed the ultrafast charge separation between daunomycin and aromatic amino acid residues of the protein, tryptophan(s). Electron transfer occurs from tryptophan(s) to daunomycin with two reaction times, 1 ps and 6 ps, depending on the local complex structure. The formation of anionic daunomycin radical is crucial for triggering a series of chemical reactions in redox cycling. One of the subsequent reactions is the reduction of dioxygen to form active superoxide by the reduced daunomycin. This catalytic process was found to occur within 10 ps. In the absence of dioxygen, charge recombination takes a much longer time, more than 100 ps. These results, along with similar findings in DNA and nucleotides, elucidate that the ultrafast generation of reduced daunomycin radicals by photoactivation is a primary step for the observed photoenhancement of drug cytotoxicity by several orders of magnitude. We also studied the dependence of the dynamics on protein conformations at different ionic strengths and denaturant concentrations. We observe a sharp transition from the tertiary structure to the unfolding state at 2 M of denaturant concentration.